'Many Nice People': the nation-state, post-Fordism, and the policy norm of flexible ethnic relations in Estonia - Feldman, Gregory (International journal of cultural policy : CP, 2010)
This article uses historical research and ethnographic fieldwork to ask how policymakers interpret historical, political, and economic factors to construct inter-ethnic communities that would bring security and economic growth to an enlarged European Union (EU). Focusing on post-Soviet Estonia's ethnic integration policy, the article argues that 'flexibility' applies not only to post-Fordist, individualized subjects, but also to relations between subjects of different nationalities that policymakers want to form organically in service sector employment. The article explains how this policy construction emerged in light of Estonia's historical trajectory from 1991 to 2001 and demonstrates how it conceptually resolved the fundamental tension between the territorialized nation-state and deterritorialized global capitalism. A visual media campaign entitled 'Many Nice People: Integrating Estonia' captured the essence of this construction, which obscured how the Estonian nation-state marginalized minorities while integrating into the EU.